2014
DOI: 10.1248/bpb.b13-00628
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inhibitor of I-KappaB Kinase Beta Ameliorates Experimental Arthritis through Downregulation of Proinflammatory Cytokines in Arthritic Joints

Abstract: Key words inhibitor of kappaB kinase beta; inhibitor; arthritis; nuclear factor-kappaB; tumor necrosis factor alpha Rheumatoid arthritis (RA) is a systemic autoimmune disease that is characterized by the chronic inflammation of joints, leading to synovial hyperplasia, infiltration of leukocytes, and progressive destruction of cartilage and bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…McIntyre and co-workers investigated the protective effect of BMS-345541, an IKKβ inhibitor, and found that it could suppress the IL-1β level to attenuate inflammation and joint destruction, contributing to alleviate collagen-induced arthritis in the mouse model 117 . The similar result was observed in the rheumatoid arthritis through inhibiting the IKKβ activity by 4-[6-(cyclobutylamino)imidazo[1,2- b ]pyridazin-3-yl]-2-fluoro- N -([(2 S ,4 R )-4-fluoropyrrolidin-2-yl])methylbenzamide 118 . Furthermore, the selective IKKβ inhibitor SC-514 inhibited the IκBα degradation to inactivate the NF-κB signal, further triggering to impair RANKL (receptor activator of nuclear factor-κB ligand)-induced osteoclastogenesis 119 , which was further supported by Thummuri's study showing that inhibition of IKKβ by abietic acid attenuated RANKL-induced osteoporosis 120 .…”
Section: Biological Potentials For Ikkβ Inhibitionsupporting
confidence: 81%
“…McIntyre and co-workers investigated the protective effect of BMS-345541, an IKKβ inhibitor, and found that it could suppress the IL-1β level to attenuate inflammation and joint destruction, contributing to alleviate collagen-induced arthritis in the mouse model 117 . The similar result was observed in the rheumatoid arthritis through inhibiting the IKKβ activity by 4-[6-(cyclobutylamino)imidazo[1,2- b ]pyridazin-3-yl]-2-fluoro- N -([(2 S ,4 R )-4-fluoropyrrolidin-2-yl])methylbenzamide 118 . Furthermore, the selective IKKβ inhibitor SC-514 inhibited the IκBα degradation to inactivate the NF-κB signal, further triggering to impair RANKL (receptor activator of nuclear factor-κB ligand)-induced osteoclastogenesis 119 , which was further supported by Thummuri's study showing that inhibition of IKKβ by abietic acid attenuated RANKL-induced osteoporosis 120 .…”
Section: Biological Potentials For Ikkβ Inhibitionsupporting
confidence: 81%
“…Activation of NFB family of transcription factors results in the expression of numerous genes involved in the regulation of the innate and adaptive immune responses, and has been implicated as a key mechanism in RA [32]. Previous data have demonstrated that selectively blocking NFB promoter activity and NFB-driven production TNF␣and interleukin-6 inhibited arthritis progression even when treatment occurred after disease development [33].…”
Section: Discussionmentioning
confidence: 99%
“…The p50/p65 form is the most common combination form (5). Various studies have shown that NF-κB participates in the transcription of genes regulating apoptosis and hyperplasia (6).…”
Section: Introductionmentioning
confidence: 99%